Self-Esteem and its Correlates to Academic Performance Among University Freshmen Students - Hernandez, Rogelio; Bernal, Merlene; Olea, Melanio (Social Sciences and Development Review, 2019)
Self-esteem is a personal opinion of an individual about herself/ himself and the appreciation of his/her worth. It refers to an accurate, justified, balanced appreciation of one’s worth as a person. However, it can also refer to inflated, grandiose, unwarranted sense of conceited superiority over others. Although it is assumed that self-esteem is a trait that is innate and stable across time within a person, studies have shown that it may notbe the case sometimes. Some experts argued that this trait can be influenced by some factors such as family, peers, environment and school. Likewise, self- esteem is believed to have a relationship with the socioeconomic status, health and health related behavior, and self- efficacy. Reports and studies have implicated the significance of self esteem to academic performance or achievement. Hence, the present undertaking was conducted to determine this line of argument. The result of the study indicated that both male (Mean=2.745) and female (Mean=3.3) students showed positive perception of their self-esteem. When the perceived self- esteem of the male was compared with the female counterpart, using the Pearson Product Moment, the obtained value of r at p≤0.05 is 0.948. The research showed a very high correlation based on Munro’s strength of correlation coefficients. However, the perceived self-esteem of both, male and female respondents showed a low correlation with their academic performance (r=0.42).
Keywords: self-esteem; self-concept; self-image; efficacy; self-worth; academic performance